Crime or social harm? A dialectical perspective - Lasslett, Kristian (2010)
This paper proposes to examine some of the core philosophical issues to have arisen out of the recent calls to move "beyond criminology". It will be claimed that the dismissal of crime as a "fictive event" is premature, as crime does indeed have an "ontological reality". Nevertheless, it will be asserted that the relation between harm and crime is contingent rather than necessary. Accordingly, this paper will argue that there is merit to the claim that we should unify research on social harm through the creation of a new field, a step which would have the added benefit of constructing an alternative venue for crimes of the powerful scholars who wish to explore the destructive practices of states and corporations unconstrained. This paper, therefore, will also offer a dialectical definition of social harm based upon classical Marxist strains of ontological thought.